1996
DOI: 10.1302/0301-620x.78b5.0780761
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Latissimus Dorsi for Irreparable Rotator-Cuff Tears

Abstract: We treated 12 shoulders in ten patients with irreparable rotator-cuff tears by transfer of the latissimus dorsi. There were nine men and one woman. Their average age was 64.0 years and the average follow-up was 35.6 months (26 to 42).The results were excellent in four shoulders, good in four, fair in one, and poor in three. Active forward flexion improved from a preoperative average of 99°t o a postoperative average of 135°. Osteoarthritic changes appeared in five shoulders and proximal migration of the humera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
130
0
20

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(175 citation statements)
references
References 15 publications
(27 reference statements)
14
130
0
20
Order By: Relevance
“…5). The gain in active elevation is high (+70°) while the gain in active external rotation (+36°) is similar or superior to that reported with the standard two-incision procedure [1,2,11,18,23,30,35,47]. As observed in our early experience with the RSA, without the tendon transfer patients would remain disabled, because in the absence of external rotator cuff muscles (infraspinatus and teres minor) there is no counterbalance to the strong functional internal rotators (pectoralis major, latissimus dorsi, teres major and subscapularis).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…5). The gain in active elevation is high (+70°) while the gain in active external rotation (+36°) is similar or superior to that reported with the standard two-incision procedure [1,2,11,18,23,30,35,47]. As observed in our early experience with the RSA, without the tendon transfer patients would remain disabled, because in the absence of external rotator cuff muscles (infraspinatus and teres minor) there is no counterbalance to the strong functional internal rotators (pectoralis major, latissimus dorsi, teres major and subscapularis).…”
Section: Discussionsupporting
confidence: 68%
“…None of our patients could control the spatial positioning of their arm, as demonstrated by positive preoperative dropping, lag, and hornblower signs. Review of the literature suggests the reported gain in active external rotation after an isolated transfer of the LD is modest, but patient satisfaction remains high because the arm is stabilized by the transfer [1,2,18,23,30,35,47]. Gerber [19] has recently reported a similar series of patients treated with a LD transfer and reverse shoulder arthroplasty; his preliminary results suggested similar promise but demonstrated a lower gain in external rotation.…”
Section: Discussionmentioning
confidence: 99%
“…For treatment of posterosuperior rotator cuff tears, Gerber et al [8,11] and others [1,12,16,23] have described transfer of the latissimus dorsi tendon sutured to the insertion site of the supraspinatus tendon using a twoincision technique.…”
Section: Discussionmentioning
confidence: 99%
“…It now is standard practice to perform muscle transfer for treatment of irreparable posterosuperior cuff tears [1,3,12]. With these surgeries, satisfactory results can be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation